Efficacy and safety of Argatroban in patients with acute ischemic stroke: a systematic review and meta-analysis - Cheng, YiRan; Liu, ChangNing; Li, ShanShan; Meng, Miao Miao; Li, He (Frontiers in Neurology, 2024)
Objective Argatroban is a highly promising drug for the treatment of acute ischemic stroke (AIS), but there is currently insufficient strong evidence regarding the efficacy and safety of using Argatroban in the treatment of AIS. Therefore, we conducted a systematic review and meta-analysis to evaluate the effectiveness and safety of Argatroban in the treatment of AIS. Methods Articles on PubMed, Embase and the Cochrane Library databases were searched from these websites’ inceptions to 2th February 2023. Randomized controlled trials and observational studies on Argatroban therapy for acute ischemic stroke were included. Meta-analyses were conducted using a random-effects model. Results Fourteen studies involving 10,315 patients were included in the meta-analysis. The results showed a significant reduction in the rate of early neurological deterioration (END) in the Argatroban group compared with the control group (OR = 0.47, 95% CI: 0.31–0.73, I2 = 15.17%). The rates of adverse events were no significant difference between the two groups (ICH: OR = 1.02, 95% CI: 0.68–1.51, I2 = 0.00%; major extracranial bleeding: OR = 1.22, 95% CI: 1.01–1.48, I2 = 0.00%; mortality: OR = 1.16, 95% CI: 0.84–1.59, I2 = 0.00%). However, the rates of mRS score of 0–1 (OR = 1.38, 95% CI: 0.71–2.67, I2 = 77.56%) and mRS score of 0–2 (OR = 1.18, 95% CI: 0.98–1.42, I2 = 0.00%) during the 90 days did not significantly improved in the Argatroban group. Subgroup analyses showed that the rate of END (OR = 0.41, 95% CI: 0.26–0.65, I2 = 2.77%) and mRS score of 0–2 (OR = 1.38, 95% CI: 1.06–1.81, I2 = 0.00%) had significantly improved when the intervention group adopted Argatroban plus Antiplatelet. Conclusion Argatroban can improve neurological deterioration, with a low incidence of adverse events such as bleeding and death, and general analysis showed no improvement in mRS. However, subgroup analysis suggests that compared to mono-antiplatelet therapy, combination therapy of Argatroban combined with antiplatelet therapy significantly reduced the incidence of END and improved mRS scores. After using Argatroban, there was no increase in the risk and mortality of intracranial hemorrhage and other bleeding sites.